Spatial-temporal metrics to assess collective behavior in football: A systematic review and assessment of research quality and applicability - Corsie, M.; Craig, T.; Swinton, P. A.; Buchanan, N. (Journal of Athletic Enhancement, 2021)
Extensive research has been conducted to investigate collective behavior of football players using spatial-temporal data. The purpose of this systematic review was to synthesize and evaluate the applicability of this research by reviewing information presented in previous studies and its capacity to clearly describe the analysis approaches and practical applications of findings. 85 studies were included in the review with approaches assigned to 4 categories of metrics (1: Spaces; 2: Distances; 3: Position; 4: Numerical relations) and 2 analysis methods (1: Predictability 2: Synchronization). The review identified that authors descriptions of metrics generally focused on operationalized definitions and provided limited translation to game scenarios or coaching strategies. Similarly, a substantive percentage of studies (22%) did provide any practical applications, and where these were provided, they were generally broad and provided limited actionable information that could be used directly by practitioners to inform training. Where specific applications were provided these were consistent with a dynamic systems perspective of collective behavior and focused on organismic, environmental and task constraints that could be manipulated. The findings of the present review highlight the innovative practices of the research base and identify several areas for development to increase understanding and uptake in practice.